2014
DOI: 10.1155/2014/379537
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a Decreases High Glucose/Thrombin-Induced Endothelial Inflammation by Inhibiting NAPDH Oxidase 4 Expression

Abstract: Diabetes is associated with hyperglycemia and increased thrombin production. However, it is unknown whether a combination of high glucose and thrombin can modulate the expression of NAPDH oxidase (Nox) subtypes in human aortic endothelial cells (HAECs). Moreover, we investigated the role of a diabetes-associated microRNA (miR-146a) in a diabetic atherothrombosis model. We showed that high glucose (HG) exerted a synergistic effect with thrombin to induce a 10.69-fold increase in Nox4 mRNA level in HAECs. Increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 52 publications
6
71
0
Order By: Relevance
“…However, the function of miR-146a-5p is poorly understood in endothelial cells treated by transient high glucose. In this study, we found that high glucose could decrease the expression of miR-146a-5p in HAECs, as previously reported (26). Furthermore, this decrease of miR-146a-5p persisted even the HAECs was not in the condition of the previous high glucose.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the function of miR-146a-5p is poorly understood in endothelial cells treated by transient high glucose. In this study, we found that high glucose could decrease the expression of miR-146a-5p in HAECs, as previously reported (26). Furthermore, this decrease of miR-146a-5p persisted even the HAECs was not in the condition of the previous high glucose.…”
Section: Discussionsupporting
confidence: 91%
“…Villeneuve et al provided miR125b increased in the vascular smooth muscle cells of diabetic db/db mice (25); our data showed that miR-125b also increased in HAECs treated with transient or persistent high glucose. Wang et al identified treatment with high glucose significantly decreased miR-146a expression in HAECs, as our reported (26). NF-B is a transcription factor which is able to further stimulate expression of many inflammatory genes (27), and has turned out to play an important role in the pathogenesis of atherosclerosis (28,29).…”
Section: Discussionsupporting
confidence: 73%
“…Expression of immune-modulatory miRNAs, especially miR-146a, has been determined in different diabetic complications, [48][49][50][51][52] including DN. 49,[53][54][55] While some studies have shown lower miR-146a expression during DN, 49 others have shown higher expression.…”
Section: Discussionmentioning
confidence: 99%
“…5) and new contributions to immune function and miR regulation are being discovered on an ongoing basis [216][217][218][219][220]. Understanding the molecular mechanisms of thrombin contribution to metastasis may help to develop efficient therapy and combat cancer.…”
Section: Discussionmentioning
confidence: 99%